Fever integrates antimicrobial defences, inflammation control, and tissue repair in a cold-blooded vertebrate - Farah Haddad; Amro M Soliman; Michael E Wong; Emilie H Albers; Shawna L Semple; Débora Torrealba; Ryan D Heimroth; Asif Nashiry; Keith B Tierney; Daniel R Barreda (eLife, 2023)
Multiple lines of evidence support the value of moderate fever to host survival, but the mechanisms involved remain unclear. This is difficult to establish in warm-blooded animal models, given the strict programmes controlling core body temperature and the physiological stress that results from their disruption. Thus, we took advantage of a cold-blooded teleost fish that offered natural kinetics for the induction and regulation of fever and a broad range of tolerated temperatures. A custom swim chamber, coupled to high-fidelity quantitative positional tracking, showed remarkable consistency in fish behaviours and defined the febrile window. Animals exerting fever engaged pyrogenic cytokine gene programmes in the central nervous system, increased efficiency of leukocyte recruitment into the immune challenge site, and markedly improved pathogen clearance in vivo, even when an infecting bacterium grew better at higher temperatures. Contrary to earlier speculations for global upregulation of immunity, we identified selectivity in the protective immune mechanisms activated through fever. Fever then inhibited inflammation and markedly improved wound repair. Artificial mechanical hyperthermia, often used as a model of fever, recapitulated some but not all benefits achieved through natural host-driven dynamic thermoregulation. Together, our results define fever as an integrative host response that regulates induction and resolution of acute inflammation, and demonstrate that this integrative strategy emerged prior to endothermy during evolution.